Portable Soil EC - Development of an electronic device for determining soil electrical conductivity. - RAUBER, L. A. (2024)
Decision-making in agriculture demands continuous monitoring, a factor that propels the advancement of tools within Agriculture 4.0. In this context, understanding soil characteristics is essential. Electrical conductivity (EC) sensors play a pivotal role in this comprehension. Given this backdrop, the core motivation of this research was developing an accessible and effective electronic device to measure the apparent EC of the soil. It provides features like geolocation, recording of the date and time of collection, expandable digital storage capacity, and USB connectivity, making it a valuable tool for field surveys in the application of PA. The project focused on developing an electronic circuit, starting with a schematic detailing the component connections. Reading the manufacturer's data sheets is essential to avoid mistakes. Subsequently, the printed circuit board layout was designed, considering the optimization of space and centralized positioning of the main components. The present research yielded that the portable EC meter, which demonstrates versatility in its application, is easy to handle and offers promising results for field application. The name proposed by the developers is Portable Soil EC. Field testing revealed significant variability in the soil EC in apple plantations.